Evaluation of a feasible educational intervention in preventing early childhood caries - Marina Sousa AZEVEDO; Ana Regina ROMANO; Marcos Britto CORREA; Iná da Silva dos SANTOS; Maximiliano Sérgio CENCI (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Early childhood caries (ECC) in the primary dentition of preschoolers remains high. Young children have limited access to oral healthcare, and oral health education (OHE) measures can be a valuable tool to prevent caries in this population. The aim of this study was to evaluate the impact of an early educational intervention on ECC prevention. The study group (SG) comprised 271 children aged 0-12 months and their mothers, who attended 12 selected public health centers (PHC). The SG received oral health instructions from a pamphlet and by verbal explanation of some topics. One year later, a similar sample of children from another 12 PHCs were selected to serve as the control (CG; n = 251). The children were examined to determine their caries status: decayed = cavitated and/or white spot lesion (maxillary anterior surface); missing; and filled surface index > 0. There was a one-year follow-up. Socioeconomic and demographic information was collected. Logistic regression was used to estimate the effects of the educational intervention on the ECC odds. A sample of 445 (SG = 194 and CG = 251) children remained to the end of the study and were examined. The prevalence of caries was 12.9% in the SG and 17.9% in the CG. The odds of caries were 80% higher in the CG than in the SG (p = 0.037). The strategy of providing OHE from a pamphlet and with a brief verbal instruction to mothers during their child's first year of life can constitute a valuable tool for ECC prevention.